Public power and competition law. Looking for efficiency in competition law enforcement - Canedo Arrillaga, María Pilar (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Competition law has experienced a dramatic change in former times trying to reach a higher level of effectiveness in protecting general interest. In doing so, it looks for ways to monitor burdens to competition that can be created, maintained or not removed by Public Powers (as policy makers or enforcers). This control can come from different areas of the legal order and, if using a competition law perspective, it can use an advocacy or enforcement approach. This study analyses the relation among all those possible reactions of the legal system and concludes that, looking for efficiency, it must be one of interdependence and mutual reinforcement instead of one of exclusion.
Keywords: competition; advocacy; enforcement; public Powers; better regulation; social welfare; administration; challenge in court of rules and administrative acts; facilitator